Implementasi Sistem Enterprise Resource Planning (ERP) pada PT XYZ dengan Menggunakan Modul Inventory Odoo - Aura Diva Shafa Dharma; Akmal Suryadi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In an increasingly competitive business environment, research and development companies, especially in the agro-industrial sector, need to maintain operational efficiency and competitiveness by having an integrated management system. Enterprise Resource Planning (ERP) has become an effective solution in automating business processes. This study aims to analyze the implementation of the Odoo Inventory module at PT XYZ, focusing on inventory management and its impact on efficiency, decision making, and customer satisfaction. The research method used is descriptive qualitative involving interviews, literature study, and data collection through observation. The implementation of Odoo's Inventory module successfully overcomes the constraints of warehouse operations by providing features such as Receipt Product, Internal Transfer, Scrap Orders, and Inventory Adjustments. Thus, the company can track, manage, and adjust inventory efficiently, overcome recording errors, and increase transparency in inventory management. The results show that the implementation of ERP through Odoo Inventory module at PT XYZ brings significant benefits in improving operational efficiency and inventory management. The study recommends further evaluation of user acceptance of the implemented system as well as regular updates to the latest version of Odoo software. This study provides a better understanding of the benefits of ERP implementation in the context of research and development in the agro-industrial sector and identifies potential for further research in this area.